2016
DOI: 10.18632/oncotarget.9394
|View full text |Cite
|
Sign up to set email alerts
|

The retinal determination gene network: from developmental regulator to cancer therapeutic target

Abstract: Although originally identified for its function in Drosophila melanogaster eye specification, the Retinal Determination Gene Network (RDGN) is essential for the development of multiple organs in mammals. The RDGN regulates proliferation, differentiation and autocrine signaling, and interacts with other key signaling pathways. Aberrant expression of RDGN members such as DACH, EYA and SIX contributes to tumor initiation and progression; indeed, the levels of RDGN members are clinically prognostic factors in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 95 publications
7
28
0
Order By: Relevance
“…Exciting outcome of molecular targeting therapy is driving the need for better understanding the tumor biological features of each patient (7). Recent evidence has linked RDGN family with the progression of various cancers, indicating it might be a potential therapeutic target for precision medicine (11)(12)(13)(14)(15)(16)(17)(18)25). In the present study, our results first showed that SIX1 protein elevated in thyroid malignant tumor.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Exciting outcome of molecular targeting therapy is driving the need for better understanding the tumor biological features of each patient (7). Recent evidence has linked RDGN family with the progression of various cancers, indicating it might be a potential therapeutic target for precision medicine (11)(12)(13)(14)(15)(16)(17)(18)25). In the present study, our results first showed that SIX1 protein elevated in thyroid malignant tumor.…”
Section: Discussionsupporting
confidence: 58%
“…Most recent study found the microRNA-548a-3p/SIX1 axis strongly linked aerobic glycolysis to carcinogenesis (17). SIX1 and EYA can integrate with other signal pathways to modulate the apoptosis, cell proliferation and tumor growth (18). To date, the profiles of SIX1 and EYA1 have been independently identified as a prognostic biomarker in breast cancer (13,19).…”
Section: Introductionmentioning
confidence: 99%
“…DACH1 is a key member of the retinal determination gene network, a group which affects cell cycle regulation and cancer cell growth, EMT, invasion, and migration in a context‐specific manner . Its reduced expression is observed in several types of cancer, mostly associated with poor prognosis . Our results also point that these TFs' inferred activity is repressed in lung adenocarcinoma, similarly to previous lung cancer studies .…”
Section: Discussionsupporting
confidence: 88%
“…These genes may control the expression levels of other variegation modifiers. In addition, both Six4 and Tsh are members of the “retinal determination network (RDN),” a collection of genes whose roles were originally characterized in studies of Drosophila eye development (Datta et al 2011) but which is now known to control cell specification and cell proliferation in multiple developing epithelia in Drosophila and mammals (Kong et al 2016). Thus, changes in the expression of tsh or Six4 in follicle progenitors either directly or indirectly affect progenitor proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%